Peningkata Kinerja Tenaga Edukatif di Bidang Pariwisata - Farid Said (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2009)
This paper discusses "Makasar Tourism Training Project" (MTTP) which aims to increase the human resources performances for tourism. Many programs have been implemented by this project such as Competency Based Training/ Assessment Workshop; Fellowship Programs; Training Programs; and Upgrading Facilities. This paper show that MTTP have succeeded in increasing the tourism performance particularly and human resources for tourism in wider sense. However, various obstacles found this program, such as: lack of commitment in the parts of local government, insufficient, and poor motivation. These obstacles have to be tackled in order to ensure the program sustainability.